THE INFLUENCE OF TENNIS ON THE FORMATION OF HUMAN FUNCTIONAL SYSTEMS (World Bulletin of Public Health, 2023)
Tennis is one of the most effective means of maintaining vitality and improving health. In addition to physical activity, it also gives a great emotional charge, creates a good mood and gives a sense of satisfaction with one's activity, which is no less important than physical activity.
Keywords: tennis; physical culture; sports; education